PROMIS® and Neuro-QoLTM measures are valid measures of health-related quality of life among patients with familial chylomicronemia syndrome. (2nd April 2020) - Fox, Rina S.; Peipert, John Devin; Vera-Llonch, Montserrat; Phillips, Glenn; Cella, David
ABSTRACT: Background: FCS significantly affects health-related quality of life (HRQOL). Legacy patient-reported outcome measures are often not sensitive to FCS's impact. NIH PROMIS and Neuro-QoL measures may accurately capture HRQOL in FCS patients. This study assessed a broad range of PROMIS and Neuro-QoL measures covering physical, mental, and social HRQOL to determine their suitability for the FCS population. Methods: Adult FCS patients in the United States ( N = 25) were recruited to an online survey study and completed several PROMIS short forms and Neuro-QoL computer adaptive tests. Results: Scores were more than 0.5 standard deviations ( SD ) worse than the normative mean on 10 of 16 normed measures, and more than 0.75 SD s worse than the normative mean on two measures. Responses at the floor and ceiling were occasionally observed, marginal reliabilities were strong, and significant differences across performance status ( p s < 0.05) provided preliminary support for construct validity. The measures correlated with each other strongly and as expected. Conclusion: Results support the ability of PROMIS and Neuro-QoL measures to detect HRQOL impairment among patients with FCS. PROMIS and Neuro-QoL measures captured the functional impact and symptom burden associated with FCS, and the broad range of symptom severity experienced by patients with FCS.